Bridging mobile security gaps. Issue 1 (January 2016) - Shaulov, Michael
Abstract : Moving targets may be harder for attackers to hit, but the allure of cold hard cash and geopolitical influence are powerful incentives for them to improve their aim. In the past year, the rate of attacks on iOS devices has escalated rapidly, including nine major attacks like WireLurker, PawnStorm and XCodeGhost. On Android, the situation is much more dire with over 10 new, sophisticated attacks in four months alone including Ghostpush and Braintest. Hackers and cyber-criminals are now focusing much of their efforts on mobile platforms, often as a first step to breaking into corporate networks. There are plenty of point solutions offered by the security industry, but many of the vulnerabilities lie in the gaps in the protections they offer. Michael Shaulov of Check Point examines what protective measures exist and how to fill those gaps to give the right balance of protection, mobility and productivity.